Entre cuidados e contradições: representações sociais de trabalhadoras e trabalhadores sobre uma unidade de acolhimento - VANESSA DUARTE (2025)
The study aimed to analyze the social representations (SR) of workers at an institutional shelter unit in the city of Campo Grande (MS), Brazil, regarding the institution where they work. To this end, the theoretical foundation adopted was the Social Representations Theory (SRT), which helps understand how individuals construct and share meanings about the reality they experience. This is a qualitative study, as this methodological approach allows for capturing the complexity and subjectivity inherent to social representations, considering the subject-object dynamic in knowledge construction. For data collection, two methods were used: semi-structured individuais interviews, which allowed for an in-depth exploration of individual perceptions, and group discussions, which fostered collective expression and group interaction. The organization of the results was carried out using Bardin's Content Analysis technique. For data analysis, SRT was applied as a systematic procedure to categorize and interpret the discourses, identifying thematic cores and contradictions in the participants' statements. The results revealed ambiguous and paradoxical social representations regarding the shelter unit, expressed in the following categories: 1) Welcoming and Monitoring, 2) Charity, 3) Family-like, 4) Difficult but Rewarding, and 5) Guilty. On one hand, workers idealize the institution as a welcoming, protective, and affective space, likening it to a familial and humanized concept. On the other hand, they describe institutional practices that resemble mechanisms of control, discipline, and surveillance, similar to prison-like structures. This duality highlights a tension between idealized discourse and operational reality, where conflicting perceptions about the institution's role coexist. Such contradiction may reflect, for example, the difficulty in reconciling social assistance work with the structural and organizational limitations of the service, as well as possible influences of social stereotypes about sheltered populations. Thus, the study contributes to a critical reflection on institutional practices, suggesting the need for greater alignment between the theoretical principles of shelter care and the daily experiences of workers, in order to promote more coherent and emancipatory practices.